Emotional Dissonance and Sickness Absence Among Employees Working With Customers and Clients: A Moderated Mediation Model via Exhaustion and Human Resource Primacy - Indregard, Anne-Marthe R.; Ulleberg, Pål; Knardahl, Stein; Nielsen, Morten B. (Frontiers in Psychology, 2018)
Emotional dissonance, i.e. a discrepancy between required and felt emotions, has been established as a predictor of sickness absence in studies, but little is known about mechanisms that can explain this association. In order to prevent and reduce the impact of emotional dissonance on sickness absence, there is a need for greater attention to variables explaining when and how emotional dissonance is related to sickness absence. The overarching aim of this study was to examine whether emotional dissonance has an indirect association with sickness absence through exhaustion and whether human resource primacy, which is the employer’s degree of concern for human resources, moderates this indirect effect. A sample of 7 758 employees, all working with customers and clients, were recruited from 96 Norwegian organizations. Emotional dissonance, exhaustion and human resource primacy were measured through surveys and then linked to registry data on medically certified sickness absence for the year following the survey assessment. Results showed that exhaustion is a mediator for the relationship between emotional dissonance and sickness absence. Furthermore, higher levels of human resource primacy were found to reduce the positive association between emotional dissonance and exhaustion, and the indirect effect of emotional dissonance on sickness absence through exhaustion was found to be weaker when human resource primacy is high. By testing this moderated mediation model, the current study contributes to the literature on emotion work by clarifying mechanisms that are crucial for the development of targeted interventions that aim to reduce and prevent sickness absence in client-driven work environments.